Education for Sustaining Peace through Historical Memory - Schultze-Kraft, Markus (Memory Politics and Transitional Justice, 2022)
Informed by the author's long-standing work on violent conflict, peace and education in countries of the Global South, particularly Colombia, this open access book presents a comprehensive narrative about the relationship between peace education, historical memory and the sustaining peace agenda, advocating for the adoption of a new perspective on education for sustaining peace through historical memory. Education on and for peace in countries wrestling with, or emerging from, protracted violent conflict is up against major challenges, and both conventional and critical approaches to peace education are limited to address these. Incorporating a focus on historical memory, without losing sight of its own pitfalls, into peace education can support learners and teachers to come to grips with achieving positive, peace-sustaining change at both the micro (individual) and macro (social and institutional) levels, and to develop concepts and practices of effective and legitimate alternatives to violence and war. Conceived in these terms, historical memory-oriented peace education also stands to enhance the work-in-progress that is the UN-led sustaining peace agenda, including its Sustainable Development Goals.